Perceptions of Ulwaluko in a Liberal Democratic State: is multiculturalism beneficial to AmaXhosa women in the Eastern Cape province of South Africa? - Gogela, Kholisa B (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2018)
This exploratory qualitative study sought to investigate the views and perceptions of women on their experiences of ulwaluko, a traditional rite practised by amaXhosa in the Eastern Cape province of South Africa. Ulwaluko is also known as isiko lokwaluka or ukoluka in isiXhosa. The concept refers not only to the act of circumcision that occurs during the initiation ritual but the entire process a boy goes through in observing this practice. Ulwaluko is performed in the belief that it will transform boys into accountable and responsible citizens of the society who are fully committed and dedicated to the tenets and standards of nation building. All amaXhosa boys are expected to undergo this tradition to be considered men. Failure to go to the initiation school usually results in social stigma and complete banishment by the society. There is an abundance of literature on studies that have been conducted on male circumcision (and not ulwaluko) which is performed for hygiene and religious purposes worldwide. With regards to ulwaluko of amaXhosa, research studies that have been conducted appear to lean mainly towards biomedical and public health aspects of the ritual. There seems to be an even bigger proportion of studies whose objective was to examine the relationship between circumcision and HIV/AIDS. From the literature review, it was not difficult to observe the pervasive paucity of research studies on women in relation to initiation (and that of amaXhosa in particular), with regards to their inclusion or exclusion in the practice, their feelings, perceptions, experiences and attitudes towards the custom. It is for this reason that I found it crucial to conduct this study. The main research question I sought to answer in this investigation was: are the human rights and gender equality rights of women, as entrenched in the multicultural principles that underpin South Africa's liberal, democratic order, adequately protected? In other words, could the individual rights of women (or gender rights) that are endorsed by liberalism, be deferred in the interest of respecting traditions and cultural values associated with ulwaluko? And if they are, I further ask: could the deferral of such rights be legitimate in the face of South Africa's legal framework? The nature of this study places it in the qualitative paradigm, and interpretive phenomenology was the most appropriate research design to carry out the investigation. Multiculturalism is a principle at the centre of liberalism, and as a framework for this study, I contrast and reconcile it with feminism. While multiculturalism is concerned with protecting traditions and cultures of minority groups, feminism is concerned about women's emancipation. I used the non-probability purposive sampling to select participants who were rich in information; and I made use of community structures to gain entry into research sites and to seek permission to carry out the investigation. I conducted the pilot study in Mdantsane, a township in the Buffalo City Municipality; and I gathered data in two research sites, namely: Flagstaff in Mpondondoland and Grahamstown in the Makana Local Municipality. I employed two qualitative methods to collect information, namely: focus group discussions (FGDs) and semi-structured in-depth interviews. A total of 70 participants took part in the study. 60 women participated in 8 focus groups and 10 participated in-depth interviews. Their ages ranged between 31 and 82 years. I recorded all the FGDs and semi-structured in-depth interviews that I conducted, for ease of transcription and translation. To interprete and analyze data, I applied the general inductive approach which I later substantiated with the use of NVivo 8, a computer assisted qualitative data analysis (CAQDAS). This resulted in the identification of four themes and their related sub-themes which I compared and contrasted with literature review and the theoretical framework, so as to make sense of the information I generated from the data collection process. I also discussed the results in line with the four goals of the study. The findings of this inquiry suggest a number of factors about ulwaluko, the following being the most significant: that firstly, although the rite is espoused and celebrated by some women as a significant cultural practice among amaXhosa, for others it is synonymous with patriarchy and hegemony. Secondly, women felt largely excluded, claiming that they were relegated to a subordinate position in society. For this reason, as well as because of the biomedical and other socio-political concerns associated with the practice, some women resented the custom. Thirdly, participants were divided about whether the practice should be continued or abolished; and these differences manifested within and between different regions. Fourthly, the results also demonstrated that the norms and values applied in ulwaluko are in contravention of the fundamental principles of a liberal state in that universal human rights are infringed upon through exclusionary practices. In this case the woman's voice is muted; and this results in the denial of human agency. The study however, also revealed the emergence of shifting patterns in some parts of the province where an effort to include women appears to be taking place. Fifth and last, the enquiry demonstrated that ulwaluko is deeply entrenched among amaXhosa; that it has stood the test of time and is unlikely to be discontinued. Based on the results, I recommend that creative and transformative ways of addressing the evident clash between the provision of individual rights by the state and the recognition of ulwaluko as a cultural practice (which is perceived by some as harmful to women) be sought. To achieve this objective I make the following recommendations: 1) establishment and utilization of gender equality programmes; 2) modification of values and norms of the custom; 3) representation of women in decision-making structures; 4) establishment of collaborative networks; 5) widening of access to services (such as chapter nine institutions and national gender machinery); 6) documentation and sharing of effective and inclusive practices as well as; 7) creating awareness on initiation legislation.
Keywords: Initiation rites -- South Africa -- Eastern Cape; Circumcision -- South Africa -- Eastern Cape; Stigma (Social psychology) -- South Africa -- Eastern Cape; Xhosa (African people) -- South Africa -- Eastern Cape; Women -- Attitudes; Multiculturalism -- South Africa -- Eastern Cape; Women's rights -- South Africa -- Eastern Cape; Male domination (Social structure) -- South Africa -- Eastern Cape; Sex discrimination against women -- South Africa -- Eastern Cape; Ulwaluko